Community-based zinc supplementation for linear growth recovery in stunted under-five children in Indonesia - Heny Yuniarti; Joko Wahyu wibowo; Shofi Khofsoftun Purjaningsih (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2025)
Stunting remains a significant nutritional challenge in Indonesia and across Southeast Asia, with zinc deficiency identified as a contributing factor to impaired linear growth in early childhood. Zinc is critical for growth hormone synthesis, bone development, and immune regulation. Despite existing intervention programs, stunting prevalence in Indonesia remained at 19.8% in 2024. This study evaluated the effect of zinc supplementation on the linear growth of stunted children aged 0–5 years attending Bangetayu and Genuk Public Health Centres in Semarang. Employing an observational analytic design with a one-group pretest-posttest approach, 42 stunted toddlers received a daily oral dose of 20 mg zinc sulfate syrup for two months. Anthropometric measurements were recorded before and after the intervention, with paired T-tests applied to normally distributed data and Wilcoxon signed-rank tests to non-normal data. After two months of supplementation, 86% of the participants demonstrated improvements in both height and weight. The mean height increased from 79.9 cm to 81.0 cm (p < 0.001), while the mean weight increased from 9.28 kg to 9.74 kg (p < 0.001). These findings indicate that zinc supplementation significantly enhances linear growth among stunted toddlers. Consequently, integrating zinc supplementation into national nutrition intervention strategies could be pivotal in reducing early childhood stunting.